The Effect of Ultrasonic Treatments on Current Transport Processes in Al-Al2O3-p-CdTe-Mo Structure - A. K. Uteniyazov; A. Y. Leyderman; M. V. Gafurova; Kh. N. Juraev; K. A. Dauletov (Advances in Materials Science and Engineering)
It was established that ultrasonic treatments (USTs) have practically no effect on the patterns of current flow in the Al-Al2O3-p-CdTe-Mo structure in the forward direction, namely, as in the absence of ultrasonic action, they appear in the sequence J∼V, J∼V2, J∼V5.3, and J∼V2. The effect of ultrasonic treatments affects only the magnitude of the flowing current; at low voltages, the current becomes somewhat larger, and at high voltages, it practically does not change. Changes in the magnitude of the flowing current are explained on the basis of the assumption that the recombination of nonequilibrium carriers in such a structure occurs through complex pair recombination complexes and, as a result of ultrasonic treatments, the number of both small acceptors and deep recombination centers increases.